2009
DOI: 10.1086/599305
|View full text |Cite
|
Sign up to set email alerts
|

Rarity, Commonness, and the Contribution of Individual Species to Species Richness Patterns

Abstract: Common species have a greater effect on observed geographical patterns of species richness than do rare ones. Here we present a theory of the relationship between individual species occurrence patterns and patterns in species richness, which allows purely geometrical and statistical causes to be distinguished from biological ones. Relationships between species occupancy and the correlation of species occurrence with overall species richness are driven by the frequency distribution of species richness among sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 42 publications
3
47
0
1
Order By: Relevance
“…; Šizling et al . ). However, rarity in this study was expressed so as to emphasize the contribution of rare species (instead of using number proportions only) while reducing the effect of the abundant ones.…”
Section: Discussionmentioning
confidence: 97%
“…; Šizling et al . ). However, rarity in this study was expressed so as to emphasize the contribution of rare species (instead of using number proportions only) while reducing the effect of the abundant ones.…”
Section: Discussionmentioning
confidence: 97%
“…Various previous studies have decomposed richness gradients based on size of species distributions (Lennon et al 2004, Vazquez and Gaston 2004, Arita and Rodriguez‐Tapia 2009, Sizling et al 2009). These studies have shown that the overall gradient is typically disproportionately dominated by the contribution of only the most broadly distributed species, and hence patterns of small ranged species have been underrepresented in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that heterogeneity is complementary to energy and seasonality along this geographic range size dimension. The idea that measures of energy, climate and productivity are the strongest correlates of richness (Field et al 2009) might be produced by studies that have used all‐species gradients and consequently have relied disproportionately on the contribution of species with broad distributions (Sizling et al 2009). Other processes, like habitat heterogeneity, might be required to explain richness patterns of species with restricted distributions (Jetz and Rahbek 2002).…”
Section: Discussionmentioning
confidence: 99%
“…and improve predictions of rare species (Lomba et al. , 2010) – the latter can prove important components of diversity (Sizling et al. , 2009) but are currently difficult to model with SDMs due to their low prevalence in datasets (Stockwell & Peterson, 2002); and (3) assessing what probability threshold should be used for converting predicted species probabilities into presence–absence information (Pineda & Lobo, 2009), and its implications for defining the species pool or developing approaches to use probabilistic predictions to reconstruct community properties directly.…”
Section: The Components Of the Framework: Current Knowledge And Futurmentioning
confidence: 99%